Hybrid U-Shaped-Microbend SMF Evanescent Wave Sensor for River Water Quality Assessment: A Preliminary Study - Amirul Hazim Kamarulzaman; Wan Maisarah Mukhtar (Faculty of Applied Sciences, Universiti Teknologi, 2024)
Indexed by MyCite